2003
DOI: 10.1002/clc.4960260103
|View full text |Cite
|
Sign up to set email alerts
|

Therapy to reduce risk of coronary heart disease

Abstract: Summary: Recent primary and secondary intervention studies have shown that reduction of low-density lipoprotein cholesterol (LDL-C) with statins significantly reduced coronary heart disease (CHD) morbidity and mortality. However, many patients with dyslipidemia who have or are at risk for CHD do not reach target LDL-C goals. The recently updated National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III guidelines identify a group of patients at very high risk for CHD for more aggressive LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…1) (1). Large scale randomized clinical trials have shown that statins provide benefits in prevention of both primary and secondary cardiovascular diseases (2)(3)(4)(5)(6). However, the striking benefit achieved with statin treatment in patients with a dynamic range of cholesterol levels suggested that effects other than lipid-lowering may also contribute to these beneficial effects observed clinically.…”
mentioning
confidence: 92%
“…1) (1). Large scale randomized clinical trials have shown that statins provide benefits in prevention of both primary and secondary cardiovascular diseases (2)(3)(4)(5)(6). However, the striking benefit achieved with statin treatment in patients with a dynamic range of cholesterol levels suggested that effects other than lipid-lowering may also contribute to these beneficial effects observed clinically.…”
mentioning
confidence: 92%
“…Statins [3‐hydroxy‐3‐methylglutaryl‐coenzyme A (HMG‐CoA) reductase inhibitors] are potent cholesterol‐lowering drugs used for the treatment of hypercholesterolaemia (Stein 2002) and coronary heart disease (Rader 2003). In addition, statins reduce stroke incidence and may also reduce the risk of Alzheimer's disease (Hess et al .…”
mentioning
confidence: 99%
“…In large clinical trials, it has been shown that the use of statins not only reduces coronary events, but also total mortality rates in patients with coronary heart disease (35)(36)(37)(38)(39)(40). Because the benefit of such a treatment is greater than expected in terms of the reduction of low density lipoprotein cholesterol levels produced, it has been proposed that statins exert actions beyond that of simply lowering cholesterol.…”
mentioning
confidence: 99%